Factors that influence Business Sustainability: Evidence from MSMEs in Papua Province, Indonesia - Muhammad Ridhwansyah Pasolo; Yaya Sondjaya; Muslim Muslim; Fitriawati Fitriawati (SEIKO : Journal of Management & Business, 2023)
This research investigates the factors influencing the business sustainability of micro, small, and medium enterprises (MSMEs) in Papua. Using 118 samples from a total population of 22,627 MSMEs in the city of Jayapura, the capital of Papua, we found that Business Capital is the main factor that has a significant favorable influence on the sustainability of MSME businesses. The other factors, namely the use of social media, financial literacy, and inclusion, do not affect the sustainability of the MSME business. This study has examined several factors that affect business sustainability, especially in MSMEs. However, from the test results, it was found that a vital factor impacting the sustainability of MSME businesses is Business Capital. Other factors, such as the use of social media, financial literacy, and financial inclusion, do not directly affect business sustainability. This means that MSMEs in Jayapura City still rely on the strength of business capital as the main factor determining business sustainability. This study used a survey of MSMEs; of course, the results have biases that can still be improved in future studies. Future research can add several measurement variables, such as technology utilization, regulatory support from the government, and other variables that are not explained in this study. Kata Kunci: Business Sustainability; Evidence; Papua Province.